2005
DOI: 10.1117/12.587105
|View full text |Cite
|
Sign up to set email alerts
|

Determining digital image origin using sensor imperfections

Abstract: In this paper, we demonstrate that it is possible to use the sensor's pattern noise for digital camera identification from images. The pattern noise is extracted from the images using a wavelet-based denoising filter. For each camera under investigation, we first determine its reference pattern, which serves as a unique identification fingerprint. This could be done using the process of flat-fielding, if we have the camera in possession, or by averaging the noise obtained from multiple images, which is the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
89
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 8 publications
0
89
0
Order By: Relevance
“…Another promising approach in this area is made by Lukas et al [5]. In their work, sensor's pattern noise is characterized via wavelet-based image denoising.…”
Section: Introductionmentioning
confidence: 99%
“…Another promising approach in this area is made by Lukas et al [5]. In their work, sensor's pattern noise is characterized via wavelet-based image denoising.…”
Section: Introductionmentioning
confidence: 99%
“…Although every camera has a unique noise pattern but the pattern noises of different cameras have some common statistical properties that are not present in computer generated images and can be used to classify the images between natural and synthetic images. Similarly the images generated by different computer graphics software will exhibit common properties that will not be present in images captured by cameras [16].…”
Section: Source Identification Approachesmentioning
confidence: 99%
“…This unique sensor noise pattern can be uniquely mapped to a source digital camera using the reference error pattern which is calculated by averaging noise pattern calculated using denoising process over a number of images captured by that particular camera [16].…”
Section: Source Identification Approachesmentioning
confidence: 99%
“…One may want to find the particular device (digital camera or scanner) which generated the image or one might be interested in knowing only the make and model of the device. As summarized in [2], a number of interesting and robust methods have been proposed for source camera identification [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In [7], it is shown that defective pixels can be used for reliable camera identification even from lossy compressed images. In [6], an approach for camera identification using the imaging sensor's pattern noise was presented. The identification is based on pixel nonuniformity noise which is a unique stochastic characteristic for both CCD (Charged Coupled Device) and CMOS (Complementary Metal Oxide Semiconductor) sensors.…”
Section: Introductionmentioning
confidence: 99%